Reliability analysis of Hydraulic Shovels (ebc38248-beae-4a24-846c-1f1fa3793478) - S. R. Dindarloo; E. Siami-Irdemoosa (Society for Mining, Metallurgy & Exploration, 2015)
"Pareto analysis was used to investigate the failures database of a Hitachi EX1900 hydraulic shovel over one year of continuous operation. The hydraulic system and hydraulic links, hoses and piping were identified as the most critical system and subsystem, respectively. A three-parameter gamma distribution function was identified as the best fit for a probabilistic modeling of the time between failures (TBFs). This distribution was used in a Monte Carlo reliability analysis of the hydraulic system. Autoregressive integrated moving average (ARIMA), within the context of a time series analysis of the TBFs, was proposed as a viable alternative to the traditional technique of distribution fitting. The mean absolute percentage error (MAPE) metric was used to compare the two models. The MAPE value that resulted from the ARIMA was 66 percent smaller than that from the traditional technique in predicting the TBFs.Resumen ¦ Se usó análisis Pareto para investigar la base de datos de fallas de una pala hidráulica Hitachi EX1900 durante un periodo de un año de operación continua. Se identificó al sistema hidráulico y a los enlaces hidráulicos, mangueras y tuberías como el sistema y subsistema más importantes, respectivamente. Se identificó una función de distribución de tres parámetros gamma como el más apto para un modelado de probabilidades del tiempo transcurrido entre las fallas (Tabes por sus siglas en inglés). Esta distribución fue usada en un análisis de confiabilidad Monte Carlo para un sistema hidráulico. El promedio de movimiento integrado auto-regresivo (ARIMA por sus siglas en inglés), dentro del contexto de análisis de serie temporal de los TBFs, fue propuesto como una alternativa viable a la tradicional técnica de ajuste de distribución. Se usó el porcentaje de la media absoluta de error (MAPE) para comparar los dos modelos. El valor MAPE que resultó de la ARIMA fue 66 por ciento menor que el resultado obtenido con la técnica tradicional de predicción de TBFs."